ДИАЛОГ ТАРЖИМАСИДА ҚАҲРАМОН ХАРАКТЕРИНИ ҚАЙТА ТИКЛАШ - Ташанов, К.Ю. (SCIENCE and SOCIETY, 2020)
The article explores the artistic component - dialogues that arosing under the influence of the psychological state of the hero and ways of their reproduction in translation. In particular, the manifestations of the hero’s character traits in dialogues were studied and from the point of view of their connection with emotions or emotional state of the characters, they are analyzed in the aspects of the dialogue-situation, dialogue-character, dialogue-national character.